Metastatic pancreatic ductal adenocarcinoma in a teenage girl: A rare disease - Sutaryo Sutaryo; Scolastika Dita Kristian (Paediatrica Indonesiana, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is highly uncommon in patients < 20 years of age, at less than 0.1% of population.1 Pancreatic tumors in children and adolescents can develop from endocrine or exocrine cells. The tumor types include solid pseudopapillary tumor, ductal adenocarcinoma, pancreatoblastoma, acinar cell carcinoma, and pancreatic endocrine neoplasm (malignant and benign).2 Other types of tumors may be attached to it or secondarily engage the gland or emerge from other kinds of non-pancreatic cells inside the pancreas. The prevalent type of classic PDAC in adults is highly uncommon in children. We report here on a fifteen-year old girl with metastatic pancreatic ductal adenocarcinoma (mPDAC), who presented with abdominal discomfort and jaundice.